Sentra Kerajinan Tenun Di Pekanbaru Dengan Pendekatan Tampilan Visual Arsitektur Melayu - Diah Ajeng Primasari; Ratna Amanati; Muhammad Rijal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Indonesian society are familiar with the art, culture and crafts that suitable with the habits, skills and needs. Tenun songket craft is one of the traditional craft in Riau’s Malay community, which in ancient times were often made by the nobles and only used by the royals. But nowadays, songket has been used by the public and became one of the craft that many tourists hunted as a souvenir of Riau Province. Therefore, riau needs for a place of Tenun Craft Center to preserve the craft from extinction and provide the information of tenun songket craft. Sentra is a small unit area that has a certain characteristic in which there are activities of the production process of a business type that produces a product. Craft is the result of human activity and creativity in the form of art and culture that has developed since long time ago. Tenun craft centers design adopts the Visual Appearance from Traditional Architecture of Malay’s Rumah Kajang and the settlement patterns of Talang Mamak tribes. And the concept "Home As the Media of Industry", is adapted to the functions likes educational activities, industry, marketing and recreation.Keywords: Traditional Architecture, Malay Craft Center, Rumah Kajang, Talang Mamak, Visual Appearance.